Biomass ash-based soil improvers: Impact of formulation and stabilization conditions on materials' properties. (10th March 2023) - Cruz, N.; Avellan, A.; Ruivo, L.; Silva, F.C.; Rӧmkens, P.F.A.M.; Tarelho, L.A.C.; Rodrigues, S.M.
Abstract: Biomass ash and sludge from pulp and paper industry have enormous potential to be recycled and used as components in soil improvers. Those materials can supply large amounts of nutrients and organic matter and its recycling avoids the need of landfilling. However, these wastes cannot be directly applied to soils. Some form of processing is required to ensure efficient soil pH correction, fertilization, guarantee soil protection, and reduce potential sanitary and environmental risks. In this study, different ash formulations (with or without addition of organic wastes) and stabilization conditions (indoors vs. outdoors) were tested to optimize physico-chemical properties of ash-based granules to be used as soil improvers. Biomass fly ash (BFA) was granulated in combination with different binding agents: distilled water, biological sludge (BS), biological sludge effluent (BSE), or composted biological sludge (CBS). All granulated materials were alkaline, ranging from pH 7.9 to 12.1. Their acid-neutralizing capacity ranged from 45 to 51 equiv. CaCO3, rendering them suitable as liming materials. Incorporation of organic materials (BS and CBS) enhanced water holding capacity (up to 38 %) and bulk porosity (up to 20 %). Stabilization outdoors resulted in a faster carbonation and consequent reduction of the granules pH. It also yielded a lower electrical conductivity and lower soluble salts content (Ca, Cl, K, and Na) than materials stabilized indoors. After processing and stabilization, some of these ash formulations fulfilled the criteria to be used as component for inorganic macronutrient fertilizers, liming materials or inorganic soil improvers under the EU Fertilizing Products Regulation. Graphical abstract: Image 1 Highlights: Fly ash from residual forest biomass combustion can be recycled to soil under the FPR. Granulation and stabilization of biomass ash optimize properties of soil improvers. Replacement of water by organic binding agents on granulation reduce clean water use. Organic materials incorporation enhances N and P content and water holding capacity. Stabilization outdoors promoted a faster carbonation and reduction of pH.